The 1872 census and the presence of free and captive africans in Espírito Santo (Ágora Journal, 2024)
In 1872, the Brazilian Empire managed to carry out its first official census. After 1822, the provinces were responsible for surveying the number of inhabitants, but these censuses took place for electoral purposes, with many frauds and errors. Previous attempts to census the Brazilian population failed and it was only in 1872 that the imperial government managed to know its population, including the number of captives, Creoles and Africans, and the number of free Africans. The census was divided into two groups: free and captive, and Africans, classified as a single nation, were the only ones who appeared in this social division. Espírito Santo concentrated few free and captive Africans, however, proportionally, captive dependence on foreigners was only behind the Province of Rio de Janeiro. This work aims to get to know the Africans who appear in the 1872 Imperial Census residing in the Province of Espírito Santo.
Keywords: Census of 1872; africans; slavery; Espírito Santo.